2006
DOI: 10.1097/01.mlg.0000205141.54471.7f
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Profiling of Oral Squamous Cell Carcinoma by Array‐Based Comparative Genomic Hybridization

Abstract: Genome-wide aCGH can be used to detect and map CNAs in OSCC tissue specimens with high resolution. These data implicate several candidate genes and gene pathways in the tumorigenesis of sporadic OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 21 publications
3
81
0
Order By: Relevance
“…Thus, the ninelocus predictive model highlights the utility of additional genomic alterations in predicting lapatinib response in head and neck cancer cell lines. Limited array-CGH studies of head and neck cancers corroborate many of these loci as candidate genes for driving the development and progression of head and neck cancer (50,51). Collectively, the sensitivity predicted from a limited set of fixed genetic alterations in a subset of head and neck cell lines suggests the potential for clinical benefit.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, the ninelocus predictive model highlights the utility of additional genomic alterations in predicting lapatinib response in head and neck cancer cell lines. Limited array-CGH studies of head and neck cancers corroborate many of these loci as candidate genes for driving the development and progression of head and neck cancer (50,51). Collectively, the sensitivity predicted from a limited set of fixed genetic alterations in a subset of head and neck cell lines suggests the potential for clinical benefit.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding the expression of BRCA1 in HNSCC, one study showed that BRCA1 immunostaining positivity was lost in 34% (26/77) of tongue cancers, which might be correlated with early-stage tumor progression (Vora et al, 2003). The results of genome-wide studies also suggest that genetic alterations at RAD51 (15q15.1) and XPC (3p25) loci may be present in HNSCC (Bockmuhl et al, 1996;Brieger et al, 2003;Partridge et al, 1999;Sparano et al, 2006;van den Broek et al, 2007). Altered RAD51 protein expression has been reported by one pilot study with twelve head and neck cancer patients (Connell et al, 2006).…”
Section: Some Hnscc Risk Factors Are Able To Inhibit Dna Repairmentioning
confidence: 94%
“…In contrast, studies using CGH found an overrepresentation of 17q in 9% to 47% of HNSCC (Bockmuhl et al, 1996;Brieger et al, 2003), and one array-CGH reported the gain of 17q21 in 33% (7/21) of oral cancer (Sparano et al, 2006). These controversial results by genome-wide analyses may be due to the physically close localization of ERBB2 (HER-2/neu) oncogene and the results need to be clarified by specifically looking at the BRCA1 gene locus.…”
Section: Some Hnscc Risk Factors Are Able To Inhibit Dna Repairmentioning
confidence: 98%
See 1 more Smart Citation
“…However, no specific mutations have been associated with head and neck cancer. Some array-based data (Sparano et al, 2006) demonstrates the copy number alterations (CNA) in regions covering FA genes BRCA1, BRCA2, FANCD2, and FANCG but no direct associations with the disease were found. In contrast, FANCA has been analyzed in arrayCGH-based study (Bauer et al, 2008), where the region 16q23-q24 (FANCA locus) showed a significant gain associated with lower survival rates in HNSCC patients.…”
Section: Wwwintechopencommentioning
confidence: 99%